A randomized, double-blind study to evaluate the acid-inhibitory effect of vonoprazan (20 mg and 40 mg) in patients with proton-pump inhibitor-resistant erosive esophagitis - Katsuhiko Iwakiri (Therapeutic Advances in Gastroenterology, 2017)
Background: Standard treatment for patients with erosive esophagitis (EE) is proton-pump inhibitors (PPIs), but some patients are resistant to PPIs. We aimed to evaluate the acid-inhibitory effects and efficacy of a novel potassium-competitive acid blocker (vonoprazan) in patients with PPI-resistant EE. Methods This randomized, double-blind, multicenter study of vonoprazan evaluated gastric and esophageal pH over a 24-hour period as the primary endpoint and EE healing rate as the secondary endpoint. Following a 7 to 14-day run-in period (lansoprazole 30 mg treatment), patients with endoscopically confirmed PPI-resistant EE received vonoprazan 20 mg or 40 mg for 8 weeks. Results Patients were randomized to receive vonoprazan 20 mg ( n = 9) or 40 mg ( n = 10). Over a 24-hour period; both groups showed a significant increase from baseline in the percentage of time gastric pH ≥ 4, referred to as pH 4 holding time ratio (HTR): an increase from 73.21% to 96.46% in the 20 mg group, and from 69.97% to 100.00% in the 40 mg group. Increases from baseline in esophageal pH 4 HTRs were not significant. The 40 mg group showed greater increases in gastric and esophageal pH 4 HTRs compared with the 20 mg group, but differences between groups were not significant. After 8 weeks’ treatment, the healing rate in subjects with baseline EE grades A–D was 60.0% (3/5 patients) in the 20 mg group and 71.4% (5/7 patients) in the 40 mg group. Vonoprazan was generally well tolerated. One patient (40 mg group) experienced four treatment-emergent adverse events (TEAEs) (unrelated to study drug), leading to study discontinuation. Conclusions Vonoprazan 20 mg and 40 mg effectively inhibited gastric acid secretion over a 24-hour period with significantly increased gastric pH 4 HTR, and resulted in an EE healing rate > 60.0% in this study. Vonoprazan treatment may be valuable for patients with PPI-resistant EE